The Effect of Green Accounting, Carbon Emission Disclosure and Operating Costs on Firm Value with the Sharia Muqashid Index as a Mediating Variable - Nasrah, Hidayati; Nugrahanti, Ar-rum Rizkiani (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2024)
The purpose of the research is to find out how green accounting, carbon emission disclosure, and operating cost impact on firm value with the help of sharia muqashid index as a mediating variable. Population of this research is Islamic comercial banks and Islamic business units registrasion with Financial Servises Authority in 2021-2023. Using the purposive sampling method, 18 entities we selected as samples with 54 observations. This research uses quantitative methods using secondary data from the OJK. This study found that the R2 value in test I was 20,96% and test II was 39,01 %. After testing this research provides results that carbon emission disclosure affects the muqashid sharia index, green accounting and operating costs have no effect on muqashid sharia index, then carbon emission disclosure and operating costs affect the firm value, and muqashid sharia, green accounting has no effect on firm value. As for mediating variable, carbon emission disclosure can influence the firm value through the muqashid sharia index.